Diagnosis of a Family with the Novel –α21.9 Thalassemia Deletion. (2nd November 2015) - Long, Ju; Pang, Wanrong; Sun, Lei; Lao, Kegan; Weng, Xunjin; Ye, Xuehe; Wu, Suping; Song, Chuanlu; Wei, Xiaoying; Yan, Shanhuo
Abstract: The Qinzhou α-thalassemia (α-thal) or –α 21.9 deletion was first described at the Qinzhou Maternal and Child Health Care Hospital, Qinzhou, Guangxi, People's Republic of China (PRC) in 2013. The molecular biological mechanism by which this allele leads to α-thal involves the deletion of a 21.9 kb DNA fragment of the α-globin gene cluster (NG_000006.1), designated as –α 21.9 . During routine screening, a new family with –α 21.9 was found by the research group. This is the first time that an adult patient with the –α 21.9 /αα genotype and a 6-month-old baby with the –α 21.9 /– – SEA (Southeast Asian) genotype were detected in one family. The discovery of this family demonstrates that there is a certain risk for the Qinzhou α-thal deletion in the southern regions of Guangxi Province, PRC. The detection of the adult patient with the –α 21.9 /αα genotype and the analysis of hematological data are important supplements for –α 21.9 research. Additionally, Hb Bart's (γ4) and Hb H (β4) were detected in the 6-month-old, confirming that the baby with the –α 21.9 /– – SEA genotype also carries Hb H disease. The analysis of this family verifies that the –α 21.9 deletion is an α + -thal allele.